Higher Education Student Migration in Canada: Interprovincial Structure and the Influence of Student Mother Tongue - Narh, Ebenezer; Buzzelli, Michael (Canadian Journal of Regional Science / Revue canadienne des sciences régionales)

(untitled) (Canadian Regional Science Association / Association canadienne des sciences régionales, 2022)
Approximately ten percent of Canadian higher education students cross provincial boundaries each year to attend college or university. Despite its size and impact, the geography of higher education student migration (HESM) is not well documented in Canada. This paper analyses Statistics Canada’s Postsecondary Student Information System (PSIS) for the academic year 2016/17. Interaction matrixes are developed and mapped to analyse both the broad geographical structure of interprovincial HESM and the impact of language, specifically student mother tongue, in shaping migration patterns. In both the overall picture of HESM and that of mother tongue, HESM generates expected patterns as well as important migration variations. Ontario and Quebec anchor the national picture and, together with others, constitute exchanges amongst contiguous provincial clusters. Unique cross-country interprovincial connections are also revealed and migration by mother tongue generates further nuances still. The paper concludes with a discussion of the implications of this work for understanding (i) migration-based integration amongst Canadian provincial higher education systems, and (ii) with further research, the multi-scalar processes and geographies of HESM for institutional and local economic policy makers.